IMPACT OF INTERNAL AND EXTERNAL FACTORS ON ISLAMIC BANKING MARKET SHARE IN INDONESIA - Yulia, Yulia; Sari, Nurma; Luthfi Fuadah, Evi Khadijah; Che Wae, Husnee; Kadir Jailani, Abdul (The Pontianak State Institute of Islamic Studies, 2024)
This study examines the influence of internal and external factors on the market share of Islamic banking in Indonesia during the period from 2011 to 2019. Internal factors consist of the number of Islamic Banks, while external factors consist of Bank Indonesia’s (BI) interest rates, inflation, and GDP. During the observation period, the data was normally distributed, with no heteroscedasticity or autocorrelation detected. However, due to multicollinearity, a stepwise regression test was conducted, resulting in the exclusion of the variables Number of Islamic Banks, CAR, and NPF.The findings of this study indicate that GDP has a negative and significant effect on the market share of Islamic banking in Indonesia, BI interest rate have a negative and significant effect on the market share of Islamic banking in the country, meanwhile inflation has a positive and significant effect on the market share if Islamic banking in Indonesia. The conducted study is consistent with Indonesia’s economic growth data from 2011 to 2019, which showed a decline compared to previous years. Therefore, Islamic banks should be cautious about external factors, as they have significant impact on the market share of Islamic banks in Indonesia.